(untitled) (Development Service Industry Management, 2023)
The article presents the theoretical foundations of anti-crisis management of an enterprise under modern business conditions. The essence and structural content of the anti-crisis management system are revealed. The features of the enterprise management system in crisis conditions are outlined. Special attention is paid to the modern substantive and functional content of anti-crisis management, the elements of which are used in the context of the implementation of bankruptcy procedures. The structural specifics of anti-crisis management are determined, in particular, the object, subject and purpose of such management are determined. Its features and principles of implementation are analyzed. The functions of anti-crisis management are updated. In the course of the study, the author’s definition of the category "anti-crisis management" is proposed, which is proposed to be understood as a set of measures aimed at minimizing the negative consequences of the crisis for the functioning of the enterprise and activating its rehabilitation potential through the formation of the adaptive capacity of its management system to changes in the external environment.